Teachers’ voices and their unions - Gavin, Mihajla; Stacey, Meghan; Fitzgerald, Scott; Wilson, Rachel; McGrath-Champ, Susan (New South Wales Teachers' Federation, 2023)
Mihajla Gavin et al. address the importance of teacher unions as the collective voice of teachers to counter policies that worsen teacher working conditions and student learning environments.